2016
DOI: 10.15388/na.2016.4.2
|View full text |Cite
|
Sign up to set email alerts
|

An elegant operational matrix based on harmonic numbers: Effective solutions for linear and nonlinear fourth-order two point boundary value problems

Abstract: This paper analyzes the solution of fourth-order linear and nonlinear two point boundary value problems. The suggested method is quite innovative and it is completely different from all previous methods used for solving such kind of boundary value problems. The method is based on employing an elegant operational matrix of derivatives expressed in terms of the well-known harmonic numbers. Two algorithms are presented and implemented for obtaining new approximate solutions of linear and nonlinear fourth-order bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The formulas are novel and they link the derivatives with their original polynomials. The expressions are given in terms of terminating hypergeometric functions of the type 4 F 3 (1). The derivatives are employed to introduce a new spectral solution for convection-diffusion equation based on the application of the spectral tau method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The formulas are novel and they link the derivatives with their original polynomials. The expressions are given in terms of terminating hypergeometric functions of the type 4 F 3 (1). The derivatives are employed to introduce a new spectral solution for convection-diffusion equation based on the application of the spectral tau method.…”
Section: Discussionmentioning
confidence: 99%
“…The principal aim of this section is to derive new formulas of the high-order derivatives of Chebyshev polynomials of the fifth-kind in terms of their original polynomials. We will show that the derived formulas involve hypergeometric functions each of type 4 F 3 (1). These hypergeometric functions can be reduced in case of deriving the first derivative formula.…”
Section: Explicit Formulas Of the Derivatives Of Chebyshev Polynomial...mentioning
confidence: 94%
See 2 more Smart Citations
“…Overall, these recent papers highlight the continued usefulness of these methods in solving FDEs. Many studies have shown how useful it is to use operational matrices (OMs) of the derivatives of OPs to solve ordinary and FDEs numerically [22][23][24][25][26][27][28][29]. The main goal of this paper is to come up with new numerical spectral solutions for some types of FDE models.…”
Section: Introductionmentioning
confidence: 99%